Importance of Corruption Prevention and Its Impact on Social Health - Hamidreza Hasanpour; Behzad Razavi (Hamadan University of Medical Sciences, 2018)
Introduction: Corruption is one of the major obstacles to achieving progress and development in the communities and countries. Hence, understanding the phenomenon of corruption, types, and measurement parameters and negative consequences of corruption in various aspects of political, administrative, social, and economic fields may help strategies to fight with corruption. Therefore, the aim of the present study was to present the definition of corruption, types, and its political, social, cultural, and administrative consequences. This study was carried out, using a documentary and library method in 2018. In this study, definitions and various categories of corruption, the general outlook of the concept of corruption and its various types, and its consequences from different aspects and relying on social health were discussed. Conclusion: Corruption has consequences such as waste of national resources, weakening incentives, preventing competition growth, increasing transaction costs, poverty, poor health, low life expectancy, unequal distribution of income and wealth, inappropriate use of domestic and foreign resources, and lack of possibility of institutional reform. Given the wide-ranging outcomes and consequences of corruption in regard of political, social, and economic in society, it is recommended to adopt efficient strategies to combat with corruption and prevent its spreads.